Pig Sample Handling in Research Laboratory Scale - Kulsum, Yuni; Adawiyah, Ayuni; Shofwaturrohmani, Fatiya; Nurjanah, Desi (UIN Sunan Gunung Djati Bandung, 2019)
The laboratory is a closed room or open room as a place for conducting experiments and research. One understanding when laboratory research is importantÂ to master is the management of samples, especially wet samples. One sample sample that requires special handling is a sample of pig. The management of samples, especially samples of unclean ingredients, do not yet have clear references so that they become a big dilemma and become uneasy with Muslims if they are not managed properly. The method used in writing this article is literature study, discussion and study. The results include laboratory layout, organizing laboratory management, and retrieval techniques as well as handling laboratory pig samples. In general, handling pig samples on a laboratory scale must be done with extra caution, detail, and aseptismÂ